Sociological social work [ - Dunk-West, Priscilla; Verity, Fiona (Ashgate, 2013)
"Sociological social work is a lifelong social work practice which is animated by a sociological perspective. Social workers 'shorthand' orientations such as 'strengths perspective', 'task centred' or 'humanistic' (to name but a few), as a way to identify their philosophical and theoretical approaches in professional life. Whilst some texts have examined sociology for social work, this text instead proposes that sociological social work is a legitimate and theoretically rich orientation, and this book demonstrates what sociological social work looks like in our rapidly changing world. This text will equip students and practitioners with a way to think sociologically, not just while they are studying, but as an ever present reference for making sense of social work purpose and how this is realised in a transforming world. This follows an established tradition in social work literature, but this book elevates and names the importance of this approach, which we argue is critically needed if social work is to achieve its agenda in transformative social, political economic and environmental contexts. The current landscape in which we live is one that is characterised by rapid changes which have implications for the life experiences of those with whom social workers work, social justice advocacy agendas, and for fulfilling the purpose of social work more generally. This book is essential reading for those looking to keep up with these changes."